An Active Parallel Filter Using PI Control - Zhang, Dazhao; Song, Yawei; Shi, Min; Tu, Hao; Ye, Zehao; Zhu, Pei (2023 3rd International Conference on Energy, Power and Electrical Engineering (EPEE), 2023)
This paper focuses on the design and implementation of active power filter (APF) with PI control. APF is a device that can effectively compensate for the harmonic and reactive power of the grid, and has the advantages of simple structure, fast response, and flexible control. We first establish the mathematical model of APF, analyze its working principle and characteristics, then design the current control strategy based on PI controller, and use proportional integral (PI) algorithm to achieve the current tracking and stability control of APF. We use MATLAB/Simulink software and an experimental platform to simulate and experimentally verify the proposed control method. The results demonstrate that the PI controller can effectively regulate the output current of APF, accomplish the compensation of harmonic and reactive power, enhance the power factor and power quality of the grid, and exhibit good robustness and anti-interference ability. This study provides a simple and effective control method for the design and application of APF.